Europe Thirty Years After 1989 : Transformations of Values, Memory, and Identity - Kavaliauskas, Tomas (Value Inquiry Book Series, 2021)
For the last thirty years the year 1989 has symbolized a European annus mirabilis , standing for such events as the fall of the Berlin Wall and the impending collapse of the Soviet Union. Cultural and political transformations in Western Europe due to the rise of the migrant crisis are now echoed in East-Central Europe. In Europe Thirty Years After 1989 , the authors jointly explore the recent history of former socialist countries such as Bulgaria, Croatia, Poland, Hungary, the Czech republic, the Baltic States, and Russia. Thirty years ago some of these countries stood as a paradigmatic example of peaceful and liberal patriotism, but during the past thirty years some countries have experienced transformations in their values, memory and identity. A shift towards illiberal democracy has occurred, although not without the overlapping trends in Western and Southern Europe. This book is for those who wish to join and learn from the search for an interpretation and answer(s) to the question: what happened to the legacy of 1989 over the past thirty years, and why did these changes and transformations occur?.